512 bit-SHA3 design approach and implementation on field programmable gate arrays - S. Neelima; R. Brindha (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
In this work, the authors consider the newly selected Hash Secure (SHA-3) algorithm on FPGA Gateway. The design is logically optimized for zone efficiency by combining the Rho steps and the one-pass algorithm. Logically recording these three steps registers leads to usage 16% of the logical resources for all implementations. This in turn reduces the latency and increases the maximum operating frequency of the project. It uses only 240 sections and has a frequency of 301.02 MHz compared to the design results with the previous FPGA implementation described in SHA3-512, the design shows the Throughput-Per-Slice (TPS) ratio of 30, 1.